Experimental Determination of the Dose of Energy Received by Seed Material after Irradiation by Electric Field - Vasylenkov, V.E.; Gudzenko, M.N. (Наука та інновації, 2020)
Introduction. Maximum use of potential biological potential of seed material is among the ways to increase the
production and to improve the quality of agricultural products. In view of the above, various methods of preseeding
treatment of seeds of agricultural crops by means of electromagnetic fields are used. At the same time
there is insufficient clarity of reproducibility of the results of radiation.
Problem Statement. However, the conventional methods for determining germination capacity require a wide
range of equipment and materials and are time-consuming. Therefore, the search for new methods of pre-seeding
treatment and the development of rapid calorimetric methods are promising directions of research.
Purpose. To study the effect of irradiation on seed material, by calorimetric methods.
Materials and Methods. To determine the caloric value of seed material, two batches of Scarlet barley seeds
are taken, one of which is irradiated with an electric field. The caloric value of the grain has been determined
using the calorimetric device B-08M, according to DSTU ISO 1928:2006.
Results. The results of quantitative indicators of temperature change of the irradiated and reference batch of
barley grain have been presented in a graphical form to visualize the effect of irradiation. The analysis of results
has shown that the non-irradiated seeds have a germination capacity of 82%, while for the irradiated seeds this
index is equal to 88%. Respectively, their caloric value is 10 842 kJ/kg and 11 985 kJ/kg, i.e. differs by 10.5%. An
experimental dependence has been established that to increase germination by 1% it is necessary to increase the
caloric value of seed mass by approximately 1.83%.
Conclusions. A 10—11% increase in the caloric value of the seeds after irradiation indicates that the
irradiation process is realized. The use of calorimetry methods can be recommended as a seed material irradiation
quality control method. Вступ. Максимальне використання потенційних біологічних можливостей насіннєвого матеріалу — це один із шляхів
збільшення виробництва та підвищення якості сільськогосподарської продукції. Зважаючи на зазначене, застосовують
різноманітні прийоми передпосівної обробки насіння сільськогосподарських культур електромагнітними
полями. При цьому спостерігається недостатня чіткість відтворюваності результатів опромінення.
Проблематика. Разом з тим, традиційні методи визначення схожості потребують широкого набору обладнання та
витратних матеріалів, тривалих термінів дослідження, тому перспективним є пошук нових методів передпосівної
обробки та розробка калориметричних експрес-методів. Мета. Вивчення реакції насіннєвого матеріалу, а саме, його енергетичної цінності до та після опромінення методами калориметрії. Матеріали й методи. Для визначення енергетичної цінності насіннєвого матеріалу було взято дві партії насіння ячменю сорту ’Скарлет’, одну з яких піддавали опроміненню електричним полем. Енергетичну цінність зерна визначали за допомогою калориметричної установки В-08 М згідно ДСТУ ISO 1928:2006.
Результати. В графічній формі подано результати кількісних показників зміни температури опроміненої та контрольної партії зерна ячменю для візуалізації ефекту опромінення. Аналіз результатів показав, що неопромінене
зерно має схожість 82 %, а опромінене — 88 %, відповідно енергетична цінність першого становила 10842 кДж/кг,
а другого — 11985 кДж/кг, тобто є на 10,5 % вищою. Встановлено експериментальну залежність, що для збільшення
схожості на 1 % необхідно збільшення енергетичної цінності насіннєвої маси приблизно на 1,83 %.
Висновки. Підвищення енергетичної цінності зерна на 10—11% після опромінення вказує на те, що процес опромінення відбувся, позитивний ефект зафіксовано. Використання методів калориметрії можна рекомендувати як спосіб контролю якості опромінення насіннєвого матеріалу.